2002
DOI: 10.1107/s0907444902004183
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of an immunoglobulin light-chain dimer with amyloidogenic properties

Abstract: The X-ray structure of an immunoglobulin light-chain dimer isolated from the urine as a "Bence-Jones protein" from a patient with multiple myeloma and amyloidosis (Sea) was determined at 1.94 A resolution and refined to R and R(free) factors of 0.22 and 0.25, respectively. This "amyloidogenic" protein crystallized in the orthorhombic P2(1)2(1)2(1) space group with unit-cell parameters a = 48.28, b = 83.32, c = 112.59 A as determined at 100 K. In the vital organs (heart and kidneys), the equivalent of the urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
4
25
0
Order By: Relevance
“…66,67 While the presence of β-strands is not essential to form this motif, several β-rich proteins (e.g., β 2 -microglobulin, transthyretin, immunoglobulin light chain especially of type λ, immunoglobulin heavy chain, concavalin A) form amyloids using the cross-β motif as seed. [68][69][70][71][72][73] In addition, Siepen et al have shown that the exposed edge β-strands in…”
Section: Sequence Differences and Similaritiesmentioning
confidence: 99%
“…66,67 While the presence of β-strands is not essential to form this motif, several β-rich proteins (e.g., β 2 -microglobulin, transthyretin, immunoglobulin light chain especially of type λ, immunoglobulin heavy chain, concavalin A) form amyloids using the cross-β motif as seed. [68][69][70][71][72][73] In addition, Siepen et al have shown that the exposed edge β-strands in…”
Section: Sequence Differences and Similaritiesmentioning
confidence: 99%
“…AL amyloidosis can occur as a primary phenomenon or in association with different forms of plasma cell disorders, such as MGUS or MM [4,15], with 10%-15% of MM patients developing an AL amyloidosis of vital organs [7][8][9][10]. In AL amyloidosis, only 18% of patients have >20% plasma cells in the BM, while the majority (60%) have <10% [6].…”
Section: Al Amyloidosis Can Be Associated With MM Lc-mm and Nonsecrmentioning
confidence: 99%
“…The molecular mass of the Bence Jones protein varies from low molecular mass fragments to 22-kDa monomers or 44-kDa dimers (20). It has been documented that the Bence Jones proteins or light chain immunoglobulins form amyloid structures, which can be stained with Congo red (21). Polymerization of such proteins into amyloid might explain the apparent protease-resistance of these urinary proteins.…”
Section: ϫ06mentioning
confidence: 99%